Perlindungan Hukum bagi Pekerja Paruh Waktu (Part-Time) dan Freelancer Menurut Regulasi Ketenagakerjaan - Bembi Satya Rhamada; Aturkian Laia (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The transformation of the labor market in the digital economy era has accelerated the growth of non-standard work arrangements, particularly part-time workers and freelancers. However, this development has not been accompanied by an adequate labor law framework in Indonesia. This article examines the legal protection afforded to part-time workers and freelancers through normative juridical research using statutory and conceptual approaches. The study finds that Indonesian labor law remains oriented toward standard employment relationships based on work, wages, and command. Part-time workers may qualify as employees but are not yet comprehensively regulated. Meanwhile, freelancers occupy a more problematic legal position. Therefore, labor law reform is needed through clearer employment classification, stronger protection of rights, and broader social security coverage for non-standard workers.